A method for preparing a surface fluorescent pattern based on large-size perovskite single crystal
By heat treatment and mechanical removal of the perovskite large-sized single crystal surface, the perovskite polycrystalline nanostructure is formed, which solves the problem of insufficient fluorescence intensity, and achieves efficient and uniform fluorescence intensity enhancement and service life extension.
Patent Information
- Application Number
- CN202410917664.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-07-10
AI Technical Summary
The application of perovskite large-size single crystals in light-emitting devices is mediocre, even worse than that of polycrystalline thin films, mainly due to the ultra-long diffusion length and ultra-low recombination rate of its carriers, resulting in insufficient fluorescence intensity.
Through the entire piece of heat treatment of the perovskite large-size single crystal surface, mechanical removal and reheat treatment of polycrystalline nanoparticles, and stamped heat treatment, a perovskite polycrystalline nanostructure with a high specific surface area is formed, which enhances its fluorescence intensity and optimizes the plane geometric characteristics.
The fluorescence intensity of perovskite large-size single crystals is significantly enhanced, which can be enhanced by up to 320 times, and a highly uniform fluorescence intensity distribution is achieved, extending the service life of high-intensity and uniform luminescence on the surface.
Smart Images

Figure CN118639334B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of perovskite technology, and in particular to a method for preparing a surface fluorescent pattern based on a large-size perovskite single crystal. Background Art
[0002] Lead halide perovskites, a class of excellent semiconductor material systems, are currently widely used in solar cells, light-emitting devices, photodetectors, and other fields. While most current optoelectronic applications are based on polycrystalline thin films, single crystals, particularly large perovskite single crystals, are still considered the material architecture that can uniquely reach the upper limit of optoelectronic performance. Essentially, given the same chemical composition, their long-range ordered lattice structure enables more thorough light absorption, longer carrier diffusion lengths, lower defect state density, better geometric control, and improved stability. Therefore, large perovskite single crystals have become an ideal target for studying the inherent physical properties of perovskite materials and provide a structural platform for the development of high-performance optoelectronic devices.
[0003] Large-scale perovskite single crystals are most commonly used in photodetectors, such as perovskite single crystal photodetectors with extremely narrow spectral response or multi-pixel, large-area sensor array imaging devices. They are also commonly used in photovoltaic devices, such as long-term stable and efficient lateral-structure perovskite solar cells or large-area, flexible, electronic bandgap cascade solar cells. Furthermore, large-scale perovskite single crystals can be used to develop other novel optoelectronic devices. These include light-bending devices with bend conductivity millions of times greater than that of traditional dielectrics, photoelectrochemical cells with high Faraday efficiencies, and electromechanical devices with mechanical energy densities far exceeding those of most existing electrostrictive materials. While large-scale perovskite single crystals have demonstrated top-tier and novel performance in these optoelectronic devices, their performance in light-emitting devices has been mediocre, even inferior to that of polycrystalline thin films.
[0004] The essence of perovskite luminescence requires rapid radiative recombination of free carriers. However, this is significantly at odds with the extremely long diffusion lengths and ultra-low recombination rates of carriers in large perovskite single crystals. Therefore, it is crucial to develop a technique to modify the surface lattice of large perovskite single crystals to significantly increase their fluorescence intensity. Furthermore, the planar geometric properties of these large crystals can be optimized to achieve spatially controlled surface fluorescence patterning applications.
[0005] Previous inventions have shown that high-intensity fluorescence is primarily concentrated at the geometric edges of perovskite single crystals, even in micron / nanostructures. This is primarily due to the disruption of the perfect lattice geometry. In principle, high-performance perovskite light-emitting devices should be based on perovskite polycrystalline nanostructures with high surface areas. Essentially, this relies on the rapid recombination of free carriers on the surface of perovskite polycrystalline nanostructures. However, this large surface area inevitably leads to extremely poor water, heat, and light stability, which severely hinders the practical application of high-performance devices.
[0006] In response to the above problems, the present invention provides a method for preparing a surface fluorescent pattern based on large-sized perovskite single crystals, which improves the luminescence intensity of large-sized perovskite single crystals, enhances their stability and sustainability, and enriches their luminescence properties. Summary of the Invention
[0007] The present invention aims to provide a method for preparing a surface fluorescent pattern based on a large-sized perovskite single crystal, the method comprising the following steps:
[0008] Step 1: Preparation of large-sized MAPbBr3 single crystals;
[0009] Step 2: Heat treatment of the entire surface of the large-sized MAPbBr3 single crystal;
[0010] Step 3: Mechanical removal of polycrystalline nanoparticles on the surface of large-sized MAPbBr3 single crystals and re-heat treatment.
[0011] Step 4: Compression mold heat treatment of the fluorescent pattern on the surface of large-sized MAPbBr3 single crystal.
[0012] Furthermore, the specific processing steps of step one are as follows:
[0013] Step 1: Prepare a saturated precursor solution by dissolving 155.18 mg of lead bromide and 44.82 mg of methylammonium bromide in 10 mL of N,N-dimethylformamide solvent and stirring at room temperature until completely dissolved.
[0014] Step 2: Dissolve 0.1 μL of polyethylene glycol in the above-mentioned precursor solution, stir at room temperature for 48 hours, and filter through a mesh with a diameter of about 40 μm to obtain a clear precursor mixed solution;
[0015] Step 3: Drop 2 μL of the precursor mixture solution onto a smooth, clean glass surface and let it sit for 1 minute.
[0016] Step 4: Place another piece of glass upside down on the droplet under its own gravity. The two layers of glass form a micron-scale cavity-like confined space. Under capillary action, the droplet gradually fills the entire cavity.
[0017] Step 5: The laminated glass is subjected to a low-temperature crystallization treatment at 50°C for 6-7 days. During this process, the solvent in the cavity slowly evaporates at the narrow gap between the glass interlayers, and the precursor gradually crystallizes into MAPbBr3;
[0018] Step 6: After the solvent is completely evaporated, separate the laminated glass vertically to obtain large-sized MAPbBr3 single crystals of multiple millimeter scale.
[0019] Furthermore, the specific processing steps of step 2 are as follows:
[0020] Step 1: Set the hot plate temperature to 110°C and maintain a dry environment. Wait until the hot plate temperature stabilizes before proceeding to step 2.
[0021] Step 2: Place a glass-based multi-millimeter-scale MAPbBr3 large-size single crystal on a hot plate. Heat is transferred from the hot plate to the crystal through the glass substrate and heated continuously for 40 hours.
[0022] Step 3: After 40 hours, the large-size MAPbBr3 single crystal is removed and placed in a room temperature environment. After natural cooling, the heat treatment of the entire piece is completed, and the fluorescence intensity is significantly enhanced.
[0023] Furthermore, the specific processing steps of step three are as follows:
[0024] Step 1: A 2 cm square smooth and clean sulfuric acid paper is horizontally covered on the surface of the MAPbBr3 large-sized single crystal with weakened fluorescence intensity by its own gravity;
[0025] Step 2: rubbing the single crystal surface horizontally with a mechanical external force of 2N for 2-3 times, and then purging the surface with nitrogen to remove the aged and decomposed perovskite polycrystalline nanoparticles from the surface of the large-sized single crystal;
[0026] Step 3: Place the large-sized MAPbBr3 single crystal on a hot plate at 110°C for 40 hours of heat treatment.
[0027] Step 4: After 40 hours, the large-sized MAPbBr3 single crystal is removed and placed in a room temperature environment. After natural cooling, the high-intensity fluorescent emitting polycrystalline nanoparticles are thermally regenerated.
[0028] Furthermore, the specific processing steps of step 4 are as follows:
[0029] Step 1: Use laser to carve a hollow pattern on the metal aluminum plate according to the preset fluorescent pattern;
[0030] Step 2: Press the aluminum mask tightly onto the surface of the large-sized MAPbBr3 single crystal and fix both sides with high-temperature tape;
[0031] Step 3: Place the molded large-size MAPbBr3 single crystal on a hot plate at 110°C for 40 hours of heat treatment;
[0032] Step 4: After 40 hours, remove it and place it in a room temperature environment. After natural cooling, remove the aluminum mask plate vertically to complete the preparation of high-contrast, high-resolution fluorescent patterns on the surface of large-size single crystals.
[0033] The present invention has the following advantages: the present invention obtains a perovskite polycrystalline nanostructure with a high specific surface area by modifying the surface of a large-sized single crystal using the proposed high-temperature heat treatment technology. The fluorescence intensity generated by the rapid recombination of free carriers on the surface of the perovskite polycrystalline nanostructure can be enhanced by up to 320 times compared with the initial single crystal surface. Moreover, due to its spatially uniform distribution characteristics, the fluorescence intensity of the entire surface of the large-sized single crystal is highly uniform.
[0034] This invention exploits the loose distribution of perovskite polycrystalline nanostructures generated by thermal etching and proposes a technique for mechanically erasing them. This procedure removes surface nanostructures that decompose and reduce fluorescence intensity after long-term storage, allowing the surface of large-scale perovskite single crystals to be exposed again. Re-heat treatment of the single crystal surface can then regenerate a new generation of high-fluorescence perovskite polycrystalline nanostructures. This strategy of mechanically erasing the MAPbBr3 MPSC surface followed by subsequent heat treatment significantly extends the actual service life of the high-intensity, uniform surface luminescence. Through repeated erasure and regeneration, the lifetime is increased to that of millimeter-scale single crystals, with each erasure consuming only a micron-thick portion of the single crystal lattice.
[0035] The present invention realizes the application of large-area and modular fluorescent patterns on the surface of large-sized single crystals. A technical means of utilizing a heavy metal mask plate is proposed, and its excellent heat conduction efficiency is used to control the thermal etching distribution on the surface of large-sized single crystals. During the heat treatment process, the surface of the sample that is not in contact with the metal plate begins to generate a perovskite polycrystalline nanostructure, thereby significantly enhancing the fluorescence intensity. The surface of the sample in close contact with the aluminum plate cannot undergo thermal etching due to the rapid heat conduction, so the surface is not affected and the fluorescence maintains its original intensity. Therefore, a high-contrast fluorescent pattern display is formed. The diversity of the fluorescent pattern is controlled by the metal template, so more complex styles can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The fluorescence photograph and fluorescence spectrum data diagram of the present invention;
[0037] Figure 2 The fluorescence image and fluorescence spectrum of the present invention;
[0038] Figure 3 This is the engraved fluorescent image diagram of the present invention. DETAILED DESCRIPTION
[0039] The present invention provides a method for preparing a surface fluorescent pattern based on a large-sized perovskite single crystal, the method comprising the following steps:
[0040] Step 1: Preparation of large-sized MAPbBr3 single crystals;
[0041] Step 2: Heat treatment of the entire surface of the large-sized MAPbBr3 single crystal;
[0042] Step 3: Mechanical removal of polycrystalline nanoparticles on the surface of large-sized MAPbBr3 single crystals and re-heat treatment.
[0043] Step 4: Compression mold heat treatment of the fluorescent pattern on the surface of large-sized MAPbBr3 single crystal.
[0044] In this embodiment, the specific processing steps of step one are as follows:
[0045] Step 1: Prepare a saturated precursor solution by dissolving 155.18 mg of lead bromide and 44.82 mg of methylammonium bromide in 10 mL of N,N-dimethylformamide solvent and stirring at room temperature until completely dissolved.
[0046] Step 2: Dissolve 0.1 μL of polyethylene glycol in the above-mentioned precursor solution, stir at room temperature for 48 hours, and filter through a mesh with a diameter of about 40 μm to obtain a clear precursor mixed solution;
[0047] Step 3: Drop 2 μL of the precursor mixture solution onto a smooth, clean glass surface and let it sit for 1 minute.
[0048] Step 4: Place another piece of glass upside down on the droplet under its own gravity. The two layers of glass form a micron-scale cavity-like confined space. Under capillary action, the droplet gradually fills the entire cavity.
[0049] Step 5: The laminated glass is subjected to a low-temperature crystallization treatment at 50°C for 6-7 days. During this process, the solvent in the cavity slowly evaporates at the narrow gap between the glass interlayers, and the precursor gradually crystallizes into MAPbBr3;
[0050] Step 6: After the solvent is completely evaporated, separate the laminated glass vertically to obtain large-sized MAPbBr3 single crystals of multiple millimeter scale.
[0051] In this embodiment, the specific processing steps of step 2 are as follows:
[0052] Step 1: Set the hot plate temperature to 110°C and maintain a dry environment. Wait until the hot plate temperature stabilizes before proceeding to step 2.
[0053] Step 2: Place a glass-based multi-millimeter-scale MAPbBr3 large-size single crystal on a hot plate. Heat is transferred from the hot plate to the crystal through the glass substrate and heated continuously for 40 hours.
[0054] Step 3: After 40 hours, the large-size MAPbBr3 single crystal is removed and placed in a room temperature environment. After natural cooling, the heat treatment of the entire piece is completed, and the fluorescence intensity is significantly enhanced.
[0055] In this embodiment, the specific processing steps of step three are as follows:
[0056] Step 1: A 2 cm square smooth and clean sulfuric acid paper is horizontally covered on the surface of the MAPbBr3 large-sized single crystal with weakened fluorescence intensity by its own gravity;
[0057] Step 2: rubbing the single crystal surface horizontally with a mechanical external force of 2N for 2-3 times, and then purging the surface with nitrogen to remove the aged and decomposed perovskite polycrystalline nanoparticles from the surface of the large-sized single crystal;
[0058] Step 3: Place the large-sized MAPbBr3 single crystal on a hot plate at 110°C for 40 hours of heat treatment.
[0059] Step 4: After 40 hours, the large-sized MAPbBr3 single crystal is removed and placed in a room temperature environment. After natural cooling, the high-intensity fluorescent emitting polycrystalline nanoparticles are thermally regenerated.
[0060] In this embodiment, the specific processing steps of step 4 are as follows:
[0061] Step 1: Use laser to carve a hollow pattern on the metal aluminum plate according to the preset fluorescent pattern;
[0062] Step 2: Press the aluminum mask tightly onto the surface of the large-sized MAPbBr3 single crystal and fix both sides with high-temperature tape;
[0063] Step 3: Place the molded large-size MAPbBr3 single crystal on a hot plate at 110°C for 40 hours of heat treatment;
[0064] Step 4: After 40 hours, remove it and place it in a room temperature environment. After natural cooling, remove the aluminum mask plate vertically to complete the preparation of high-contrast, high-resolution fluorescent patterns on the surface of large-size single crystals.
[0065] In this embodiment, Figure 1 As shown, the fluorescence photographs and fluorescence spectrum data of the large-size single crystal of MAPbBr3 before (i) and after (ii) heat treatment are recorded.
[0066] In this embodiment, Figure 2As shown, micrographs (top row) and fluorescence images (bottom row) of the surface of a large-sized MAPbBr3 single crystal that has been aged (i) after being placed in humid air (RH = 55%) for 90 days, mechanically erased (ii), and heat-treated again (iii) are recorded. The fluorescence spectra thereof under the same light excitation and signal collection window (whole piece, iv) are also recorded accordingly.
[0067] In this embodiment, Figure 3 As shown, circular array fluorescence images (i) of the surface of a large-sized MAPbBr3 single crystal after die pressing heat treatment for 40 hours, English capital characters SZU (ii), and Chinese Song typeface character "Zhang" (iii) are recorded.
[0068] Although the specific embodiments of the present invention have been described in detail in conjunction with the accompanying drawings, it should not be construed as a limitation on the protection scope of this patent. Within the scope described in the claims, various modifications and deformations that can be made by those skilled in the art without creative labor still fall within the protection scope of this patent.
Claims
1. A method for preparing a surface fluorescent pattern based on a large-size single crystal of perovskite, characterized in that: The method comprises the following steps: Step 1: Prepare large-size single crystals of MAPbBr3; Step 2: Heat treatment of the entire surface of large-size MAPbBr3 single crystal; Step 3: Mechanical removal and re-heat treatment of polycrystalline nanoparticles on the surface of large-sized MAPbBr3 single crystals; Step 4: die-casting heat treatment of the fluorescent pattern on the surface of large-size MAPbBr3 single crystal; The specific processing steps of step 4 are as follows: Step 4-1, using a laser to carve a hollow pattern on the metal aluminum plate according to a preset fluorescent pattern; Step 4-2, press the aluminum mask plate tightly onto the surface of the large-size MAPbBr3 single crystal, and fix both sides with high-temperature tape; Step 4-3, placing the molded MAPbBr3 large-size single crystal on a hot plate at 110° C. for 40 hours of heat treatment; Step 4-4: After 40 hours, remove it and place it in a room temperature environment. After natural cooling, remove the aluminum mask plate vertically, and the preparation of high-contrast, high-resolution fluorescent patterns on the surface of large-size single crystals is completed.
2. A method for preparing a surface fluorescent pattern based on a large-size perovskite single crystal according to claim 1, characterized in that: The specific processing steps of step one are as follows: Step 1: Prepare a saturated precursor solution by dissolving 155.18 mg of lead bromide and 44.82 mg of methyl ammonium bromide in 10 mL of N,N-dimethylformamide solvent and stirring at room temperature until completely dissolved. Step 2: Dissolve 0.1 μL of polyethylene glycol in the above precursor solution, stir at room temperature for 48 hours, and filter with a 40 μm diameter mesh to obtain a clear precursor mixed solution; Step 3: Drop 2 μL of the precursor mixed solution on a smooth, clean glass surface and let it stand for 1 minute; Step 4: Place another piece of glass upside down on the droplet by its own gravity, and the upper and lower glass films form a micrometer-scale cavity-like confined space. Under the capillary action, the droplet gradually fills the entire cavity; Step 5: subject the laminated glass to a low-temperature crystallization treatment at 50°C for 6-7 days. During this process, the solvent in the cavity evaporates slowly at the slit of the glass interlayer, and the precursor gradually crystallizes into MAPbBr3; Step 6: After all the solvents have evaporated, separate the laminated glass vertically to obtain large-sized single crystals of MAPbBr3 with a multi-millimeter scale.
3. The method for preparing a surface fluorescent pattern based on a large-size perovskite single crystal according to claim 1, characterized in that: The specific processing steps of step 2 are as follows: Step 1: Set the temperature of the hot plate to 110°C and maintain a dry space environment. Step 2 can be performed only after the temperature of the hot plate is stable. Step 2: Place a glass-based multi-millimeter-scale MAPbBr3 large-size single crystal on a hot stage, conduct heat from the hot stage to the crystal through the glass substrate, and heat continuously for 40 hours; Step three: After 40 hours, remove the large-size single crystal of MAPbBr3 and place it in a room temperature environment. After natural cooling, the heat treatment of the entire piece is completed, and the fluorescence intensity is significantly enhanced.
4. The method for preparing a surface fluorescent pattern based on a large-size single crystal of perovskite according to claim 1, characterized in that: The specific processing steps of step three are as follows: Step 1: Cover a 2 cm square smooth and clean sulfuric acid paper horizontally on the surface of the MAPbBr3 large-size single crystal with weakened fluorescence intensity by its own gravity; Step 2: rubbing the single crystal surface horizontally with a mechanical external force of 2N for 2-3 times, and then blowing nitrogen gas on the surface, so that the aged and decomposed perovskite polycrystalline nanoparticles are removed from the surface of the large-sized single crystal; Step 3: Place the large-size MAPbBr3 single crystal on a hot plate at 110°C for 40 hours of heat treatment; Step 4: After 40 hours, remove the large-size MAPbBr3 single crystal and place it in a room temperature environment. After natural cooling, the high-intensity fluorescent emission polycrystalline nanoparticles are thermally regenerated.
Citation Information
Patent Citations
Preparation method of perovskite fluorescent anti-counterfeit structure and perovskite fluorescent anti-counterfeit label
CN114672308A
Glaze finished product, production of glaze finished product and display device formed by using glaze finished product
JP1997087069A